Implementasi Profil Pelajar Pancasila di SDN 2 Tulungagung Kabupaten Pringsewu - Puspito, Dhimas Rinda Adi; Budiarti, Yesi; Wahyuni, Endang (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
The purpose of this study was to determine the implementation of character education for fourth grade students through the Pancasila student profile strengthening program in elementary schools, as well as how to implement character education. The study used a qualitative method with phenomenology, which was collaborated with a case study. In the process of implementing the Pancasila Student Profile, applying the characteristics contained in the Pancasila Student Profile cannot be implemented in one teaching and learning activity, but is a process because not all materials cover the six characteristics of the Pancasila Student Profile. The results of the study explain that the Implementation of the Pancasila Student Profile in Pancasila Education Learning for Class IV at SDN 2 Tulungagung, Pringsewu Regency was carried out well and in accordance with the characteristics of the Pancasila Student Profile contained in the Merdeka Belajar curriculum which was implemented through project-based learning on the proclamation process material carried out with students watching a video about the reading of the proclamation text by Ir. Soekarno, then students practice reading the proclamation text and then the mutual cooperation material, this mutual cooperation material is practiced directly by students in every activity that requires them to work together, both in learning and outside of learning.